Exchange rate fluctuations and immigrants’ labour market outcomes: New evidence from Australian household panel data - Nguyen, Ha Trong; Duncan, Alan (My University, 2017)
In this paper, we exploit plausibly exogenous changes in exchange rates across home countries over time and panel data to identify the causal impact of exchange rate fluctuations on Australian immigrants' labour market outcomes. We present new and robust evidence that, unlike immigrants in the US, those in Australia as a whole do not reduce their yearly labour market outcomes when the local currency appreciates. While female immigrants don't adjust their labour activities, male immigrants reduce their weekly labour supply and hence earn less when the Australian dollar appreciates. This work also highlights the importance of controlling for individual heterogeneity as well as gender when modelling the labour market behaviour of immigrants.
Keywords: Culture -- Immigrants; Employment; Labour market; Migration and settlement; Employment; Culture; Immigrants; Migration and settlement; Employment and unemployment